ANALISIS INTERPERSONAL SKILL MELALUI DISKUSI KELOMPOK PEMBELAJARAN IPS SISWA KELAS V MI MEDAN - Maharani, Savira (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2022)
Interpersonal skill is the ability to interact with other people, with a direct and clear communication style to build relationships with others. This study aims to describe students' interpersonal skills through Social Studies Learning Group Discussion Class V MIN 12 Medan. The approach in this study is qualitative and research procedures that produce descriptive data. The sample here is 26 students of class V MIN 12 Medan. Data collection techniques are observation, interviews, and documentation. The results showed as many as 17 students were categorized as highly skilled in interpersonal skills through group discussions, as many as 7 students in the category of skilled in group discussions and as many as 2 students in the category of moderately skilled in group discussions. It can be said that through group discussions it can be seen that the interpersonal skills of V-A MIN 12 students are in the very skilled category.